Evaluation of microwave and ultrasound extraction procedures for arsenic speciation in bivalve mollusks by liquid chromatography–inductively coupled plasma-mass spectrometry - Santos, Clarissa M. M. (2013)
Texto completo. Acesso restrito. p. 108–114